The Effectiveness of Repeated Reading Technique in Increasing EFL Students’ Reading Comprehension on Narrative Texts - Jannah, Adinda Nur Maslikhatul Jannah; Usadiati, Wahyuningsih; Jawas, Umiati (IKIP Siliwangi, 2025)
Reading ability is an important basic skill in the English language learning process. Reading not only helps students expand their vocabulary but also increases their understanding of language structures. However, many EFL (English as a Foreign Language) students still experience difficulties in effectively comprehending the content of reading passages, which impacts the development of their overall language skills. This research aimed to increase reading comprehension of narrative text by looking at the effectiveness of the Repeated Reading technique. The design used was quasi-experimental, involving sixty students of SMA Hasanuddin Wajak. The sample was divided into two groups: the experimental group, which received Repeated Reading treatment, and the control group, which did not receive Repeated Reading treatment. The instrument used in this study was a multiple-choice instrument. The data that had been obtained was analysed quantitatively using an independent sample t-test. The results stated a significant difference between students who received treatment and students who did not receive treatment. The value of (P = .000 < .05) shows that the use of the Repeated Reading method in the learning process of narrative text increases students' reading comprehension.